2018
DOI: 10.1101/402305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superresolution architecture of pluripotency guarding adhesions

Abstract: Human pluripotent stem cells (hPSC) can generate almost all adult cell lineages. While it is clear that key transcriptional programmes are important elements for maintaining pluripotency, the equally essential requirement for cell adhesion to specific extracellular matrix components remains poorly defined. Our recent observation that hPSC colonies form unusually large "cornerstone" focal adhesions (FA), distinct from parental somatic cells, that are lost following differentiation, emphasises the potential of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
2
0
0
Order By: Relevance
“…We note that a recent preprint has also reported a study of FA nanoscale architecture in human induced PSCs (hiPSCs). 71 In that study, multilayer stratification of FA proteins into ISL/ FTL/ARL was observed, supporting our notion that the multilayer architecture may be a conserved architecture of cell adhesion complexes. 28 Interestingly, on vitronectin ECM used in that study, a relatively high position of vinculin was also observed similar to our observation for mESC FAs on fibronectin and gelatin, while the inverted position of vinculin is similar to our mESC results on laminin.…”
Section: ■ Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We note that a recent preprint has also reported a study of FA nanoscale architecture in human induced PSCs (hiPSCs). 71 In that study, multilayer stratification of FA proteins into ISL/ FTL/ARL was observed, supporting our notion that the multilayer architecture may be a conserved architecture of cell adhesion complexes. 28 Interestingly, on vitronectin ECM used in that study, a relatively high position of vinculin was also observed similar to our observation for mESC FAs on fibronectin and gelatin, while the inverted position of vinculin is similar to our mESC results on laminin.…”
Section: ■ Discussionsupporting
confidence: 86%
“…We note that a recent preprint has also reported a study of FA nanoscale architecture in human induced PSCs (hiPSCs) . In that study, multilayer stratification of FA proteins into ISL/FTL/ARL was observed, supporting our notion that the multilayer architecture may be a conserved architecture of cell adhesion complexes .…”
Section: Discussionsupporting
confidence: 82%